Seasonal water storage and release dynamics of bofedal wetlands in the Central Andes - Ross, A.C.; Mendoza, M.M.; Drenkhan, F.; Montoya, N.; Baiker, J.R.; MacKay, J.D.; Hannah, D.M.; Buytaert, W. (John Wiley and Sons, 2023)
Tropical high-Andean wetlands, locally known as ‘bofedales’, are key ecosystems sustaining biodiversity, carbon sequestration, water provision and livestock farming. Bofedales' contribution to dry season baseflows and sustaining water quality is crucial for downstream water security. The sensitivity of bofedales to climatic and anthropogenic disturbances is therefore of growing concern for watershed management. This study aims to understand seasonal water storage and release characteristics of bofedales by combining remote sensing analysis and ground-based monitoring for the wet and dry seasons of late 2019 to early 2021, using the glacierised Vilcanota-Urubamba basin (Southern Peru) as a case study. A network of five ultrasound loggers was installed to obtain discharge and water table data from bofedal sites across two headwater catchments. The seasonal extent of bofedales was mapped by applying a supervised machine learning model using Random Forest on imagery from Sentinel-2 and NASADEM. We identified high seasonal variability in bofedal area with a total of 3.5% and 10.6% of each catchment area, respectively, at the end of the dry season (2020), which increased to 15.1% and 16.9%, respectively, at the end of the following wet season (2021). The hydrological observations and bofedal maps were combined into a hydrological conceptual model to estimate the storage and release characteristics of the bofedales, and their contribution to runoff at the catchment scale. Estimated lag times between 1 and 32 days indicate a prolonged bofedal flow contribution throughout the dry season (about 74% of total flow). Thus, our results suggest that bofedales provide substantial contribution to dry season baseflow, water flow regulation and storage. These findings highlight the importance of including bofedales in local water management strategies and adaptation interventions including nature-based solutions that seek to support long-term water security in seasonally dry and rapidly changing Andean catchments.
Keywords: Environmental science; Wetland; Hydrology (agriculture); Dry season; Wet season; Surface runoff; Water storage; Drainage basin; Water quality; Watershed; Water table; Discharge; Ecology; Groundwater; Geography; https://purl.org/pe-repo/ocde/ford#1.05.05